Surface roughness of Ti6AI4V after heat treatment evaluated by artificial neural networks - Altu?, Mehmet; Erdem, Mehmet; Ozay, Cetin; Bozkir, Oguz (Carl Hanser Verlag, 2016)
The study examines how, using wire electrical discharge machining (WEDM), the microstructural, mechanical and conductivity characteristics of the titanium alloy T16A14V are changed as a result of heat treatment and the effect they have on machinability. Scanning electron microscope (SEM), optical microscope and X-ray diffraction (XRD) examinations were performed to determine various characteristics and additionally related microhardness and conductivity measurements were conducted. L18 Taquchi test design was performed with three levels and six different parameters to determine the effect of such alterations on its machinability using WEDM and post-processing surface roughness (Ra) values were determined. Micro-changes were ensured successfully by using heat treatments. Results obtained with the optimization technique of artificial neural network (ANN) presented minimum surface roughness. Values obtained by using response surface method along with this equation were completely comparable with those achieved in the experiments. The best surface roughness value was obtained from sample D which had a tempered martensite structure. © Carl Hanser Verlag, München.
Keywords: Artificial neural network; Heat treatment; Surface roughness; T16A14V; WEDM